MITOS RADHIN SAGHÂRÂ DALAM KAJIAN STRUKTURALISME LEVI-STRAUSS - Dewi Angelina (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2017)
Levi-Strauss's the theory of structuralism is used as an analytical model to interpret the myth of Radhin Sahgârâ. Using this theory, there are two steps to analyze the structure of the myth. The first step, to find mytheme-mytheme in myth.In the second step, there are some figures who have an important role in the life of the community at that time, and it influenced some Madurese beliefs today. The role of Kè Polèng for Madurese, especially in Pamekasan area is a mantra for traditional healing media.Kè Polèng is believed the character that adapted the Bima's character. So, the batik craftsmen call the batik with the black-and-white characteristic as Bâtè’ Polèng. Besides, the other example that related with the myth of Radhin Saghârâis a prohibition for the fisherman to catch andkill the dolphin. The belief that is still practiced by the Madurese is a form of sacred tribute to the myths in Madura. Keyword: myth, Madurese culture, Levi-Strauss’ Structuralism.